Examining the Adoption of Metaverse and Accounting Information Systems in Business Strategy (Journal of Asian Development Studies, 2024)
This study investigates the behaviouralintention behind the adoption of Accounting Information Systems (AIS) and Metaverse technologies in small-and medium-sized enterprises (SMEs), focusing on business satisfaction as a critical mediator. With the rapidevolution of digital transformation, the integration of AIS and immersive Metaverse environments is reshaping financial transparency and customer engagement. This research extends the existing literature by integrating the Unified Theory of Acceptance andUse of Technology (UTAUT) with constructs like business satisfaction and purchase intention, addressing a gap in prior models. A quantitative, cross-sectional design was adopted, involving data collection from 286 professionals across SMEs through structured surveys. Data were analysedusing Partial Least Squares Structural Equation Modelling(PLS-SEM) via SmartPLS to examine relationships among performance expectancy, effort expectancy, social influence, and facilitating conditions. The findings reveal that business satisfaction strongly mediates the relationship between behaviouralintention and actual use behaviour. Performance expectancy emerged as the most influential predictor, while effort expectancy had a weaker effect. This research contributes to technology adoption theory by positioning business satisfaction as a central construct. The results are valuable for digital strategy developers, especially in the financial and retail sectors, aiming to integrate Metaverse and AIS platforms for sustainable business transformation